Frequency, risk factors, and outcomes of central nervous system relapse in lymphoma patients treated with dose‐adjusted EPOCH plus rituximab. Issue 11 (17th August 2017) - Malecek, Mary‐Kate; Petrich, Adam M.; Rozell, Shaina; Chu, Benjamin; Trifilio, Steven; Galanina, Natalie; Maurer, Matthew; Farooq, Umar; Link, Brian K.; Nowakowski, Grzegorz S.; Nabhan, Chadi; Ayed, Ayed O.
Abstract: Background: Central nervous system (CNS) relapse in non‐Hodgkin lymphoma (NHL) is a rare but serious complication that carries a poor prognosis. The use of infusional etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab (EPOCH‐R) for frontline treatment of diffuse large B cell lymphoma (DLBCL) is increasing, though little is known about incidence of and risk factors for CNS relapse with this regimen Patients and methods: We completed a chart review of patients with NHL who received EPOCH‐R as front line therapy. Data obtained included baseline and treatment characteristics including if patients received CNS directed therapy. We measured overall survival (OS), progression free survival (PFS), and progression to CNS involvement. Results: We identified 223 patients who met the inclusion criteria, 72% had DLBCL. Of all the patients, 5.8% experienced CNS relapse, and 38.6% were treated with CNS prophylaxis. There was no difference in rate of CNS relapse, OS, or PFS between patients who had and had not received CNS prophylaxis. Patients whose serum lactate dehydrogenase was greater than twice the upper limit of normal at diagnosis and those with extranodal disease were significantly more likely to have CNS relapse ( P  = .0247 and 0.022, respectively) than their counterparts. Conclusions: The rate of CNS relapse in this patient population approaches 6%, not significantly different from reports on those receiving R‐CHOP. The results of this study suggest that CNS prophylaxis might be more selectively used among patients treated with EPOCH‐R with certain high‐risk features.